Pengelolaan Laboratorium Komputer Dalam Mendukung Proses Pembelajaran di Madrasah Tsanawiyah (MTS) Nihayatul Amal Purwasari Karawang - Muhamad Aditya Khafid; Ilham Fahmi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research refers to the management of computer laboratories in supporting the learning process. Computer laboratory management can support the learning process of students for the better. On that basis, there are tasks and management of computer laboratories as stated in the Decree of the Minister of National Education Number 40 of 2008 concerning Standards for Facilities and Infrastructure of SMK/MAK containing minimum standards for Labkom Room: (1) minimum area of ​​computer room; (2) the minimum ratio of students; (3) the capacity of the computer room; (4) the area of ​​storage space and infrastructure; (5) computer room furniture; (6) educational equipment; (7) educational media in the laboratory room; and (8) other supporters in the laboratory room. This study aims to describe the management, the learning process, and is there any influence on the management of the computer laboratory at MTs Nihayatul Amal Purwasari Karawang